BEST PRACTICES IN CSR PROGRAMS: EMPOWERMENT OF URBAN HOME INDUSTRY ENVIRONMENTAL SUSTAINABILITY - Aziz, Abdul; Mufarika, Rully (KOMUNITAS, 2024)
The concept of an urban village aligns with the sustainability development framework by enhancing urban civilization and socioeconomic culture. However, inadequate environmental management has led to problems, such as irresponsible household industries and small and medium enterprises exacerbating socio-environmental issues through poor waste management and unsanitary food production practices. The presence of companies plays a crucial role in community development through Corporate Social Responsibility (CSR) programs. An example is the "Innovative Food Urban-Village" initiative by PT KPI RU III, which addresses urban issues. This study aims to showcase CSR best practices. It employs both qualitative and quantitative methods, using a phenomenological approach. The results demonstrate that CSR best practices effectively address issues through various innovations, including: 1) household industry waste management, 2) urban village planning, 3) creative food products, and 4) good manufacturing practices.